Tìm x, biết
a) 1/4x-1/3=5/9
b) |1/9+x|-1/3=4/9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(x-1\right)^2+8\ge8\\ A_{min}=8\Leftrightarrow x=1\\ B=\left(x+3\right)^2-12\ge-12\\ B_{min}=-12\Leftrightarrow x=-3\\ C=x^2-4x+3+9=\left(x-2\right)^2+8\ge8\\ C_{min}=8\Leftrightarrow x=2\\ E=-\left(x+2\right)^2+11\le11\\ E_{max}=11\Leftrightarrow x=-2\\ F=9-4x^2\le9\\ F_{max}=9\Leftrightarrow x=0\)
Bài 1:
a) Ta có: \(\dfrac{2}{5}\cdot x+\dfrac{1}{3}=\dfrac{1}{5}\)
\(\Leftrightarrow\dfrac{2}{5}\cdot x=\dfrac{1}{5}-\dfrac{1}{3}=\dfrac{-2}{15}\)
\(\Leftrightarrow x=\dfrac{-2}{15}:\dfrac{2}{5}=\dfrac{-2}{15}\cdot\dfrac{5}{2}\)
hay \(x=-\dfrac{1}{3}\)
Vậy: \(x=-\dfrac{1}{3}\)
b) Ta có: \(\dfrac{1}{5}+\dfrac{5}{3}:x=\dfrac{1}{2}\)
\(\Leftrightarrow\dfrac{5}{3}:x=\dfrac{1}{2}-\dfrac{1}{5}=\dfrac{3}{10}\)
\(\Leftrightarrow x=\dfrac{5}{3}:\dfrac{3}{10}=\dfrac{5}{3}\cdot\dfrac{10}{3}\)
hay \(x=\dfrac{50}{9}\)
Vậy: \(x=\dfrac{50}{9}\)
c) Ta có: \(\dfrac{4}{9}-\dfrac{5}{3}\cdot x=-2\)
\(\Leftrightarrow\dfrac{5}{3}x=\dfrac{4}{9}+2=\dfrac{22}{9}\)
\(\Leftrightarrow x=\dfrac{22}{9}:\dfrac{5}{3}=\dfrac{22}{9}\cdot\dfrac{3}{5}\)
hay \(x=\dfrac{22}{15}\)
Vậy: \(x=\dfrac{22}{15}\)
d) Ta có: \(\dfrac{5}{7}:x-3=\dfrac{-2}{7}\)
\(\Leftrightarrow\dfrac{5}{7}:x=\dfrac{-2}{7}+3=\dfrac{19}{21}\)
\(\Leftrightarrow x=\dfrac{5}{7}:\dfrac{19}{21}=\dfrac{5}{7}\cdot\dfrac{21}{19}\)
hay \(x=\dfrac{15}{19}\)
Vậy:\(x=\dfrac{15}{19}\)
a: \(x\cdot\dfrac{2}{5}+\dfrac{1}{2}\cdot x=9\)
=>\(x\left(\dfrac{2}{5}+\dfrac{1}{2}\right)=9\)
=>\(x\cdot\dfrac{9}{10}=9\)
=>\(x=9:\dfrac{9}{10}=10\)
b: \(\dfrac{1}{9}:x+\dfrac{3}{9}:x=\dfrac{5}{7}\)
=>\(\left(\dfrac{1}{9}+\dfrac{3}{9}\right):x=\dfrac{5}{7}\)
=>\(\dfrac{4}{9}:x=\dfrac{5}{7}\)
=>\(x=\dfrac{4}{9}:\dfrac{5}{7}=\dfrac{4}{9}\cdot\dfrac{7}{5}=\dfrac{28}{45}\)
a: \(\Leftrightarrow\left|x-1\right|=3-2x\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(2x-3-x+1\right)\left(2x+3+x-1\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left(x-2\right)\left(3x+2\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\)
=>x=-2/3
b: Trường hợp 1: x<-3
Pt sẽ là:
\(-x-1-x-3=10-4x\)
=>-2x-4=10-4x
=>2x=14
hay x=7(loại)
Trường hợp 2: -3<=x<-1
Pt sẽ là \(x+3-x-1=10-4x\)
=>10-4x=2
=>4x=8
hay x=2(loại)
Trường hợp 3: x>=-1
Pt sẽ là x+1+x+3=10-4x
=>2x+4=10-4x
=>6x=6
hay x=1(nhận)
a)4×(x-5)-(x-1)×(4x-3)=5
=>4x-20-4x2+7x-3-5=0
=>-4x2+11x-28=0
=>-4(x2-\(\frac{11x}{4}\)+7)=0
=>\(-4\left(x-\frac{11}{8}\right)^2-\frac{327}{16}< 0\)
=>vô nghiệm
b) (3x-4)(x-2)=3x(x-9)-3
=>3x2-10x+8=3x2-27x-3
=>17x=-11
=>x=-11/17
c)(x-5)×(x-4)-(x+1)×(x-2)=7
=>x2-9x+20-x2+x+2=7
=>22-8x=7
=>-8x=-15
=>x=8/15